New Species of Collembola (Entognatha) from Israel - Kaprus, I.Ja.; Nevo, E. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
As a result of a taxonomic study of the springtails of Mount Carmel (northern Israel), Willemia tali Kaprus’ et Nevo, sp. n. and Minotaurella edaphica Kaprus’ et Nevo, sp. n. are described. Morphological characteristics of the rare species Folsomides marchicus (Frenzel, 1941), very similar to European material, are also provided.